Insect antagonistic bio-inoculants for natural control of leaf-mining insect pests of French beans - Akello, J.; Chabi-Olaye, A.; Sikora, R.A. (African Journals Online, 2017)
Fungal endophytes, specifically, Trichoderma asperellum, Beauveria bassiana and Metarhizium anisopliae; strains M2RT4, S4SU1 and S4ST7, respectively, are known to deter aphid infestation and damage to leguminous crops, but no research exists on their biochemical profiles and effects on French bean (Phaseolus vulgaris) leaf miners. The objective of this study was to assess the ability of these endophytic bio-inoculants to produce extracellular enzymes, as well as determine their impact on French beans seedling emergence and growth, and leaf miner fecundity and pupation. Laboratory and greenhouse experiments were conduct at the International Centre of Insect Physiology and Ecology (ICIPE, Nairobi), and the University of Bonn (Germany). Bio-priming French bean seeds by soaking in fungal suspension containing 108 conidia/ ml for 4 hr positively impacted on seedling vigour. Six weeks after germination, all bio-inoculant treatments improved nodulation by 1.5-1.7 folds, while S4SU1 and M2TR4 improved shoot biomass by ~ 2g. In vitro, spore suspensions of these isolates were highly toxic to leaf miner larvae, often resulting in high mortalities and a suppression of pupation by over 70%. All tested isolates exhibited protease (Index=1.22), lipase (Index=1.32) and cellulase (Index=1.06) activities; with M. anisopliae being the best enzyme secretor when cultured under dark conditions on enzyme-specific substrate for 7-14 days. In vivo B. bassiana-primed seedlings deterred larval feeding and development, resulting in reduced number of larvae, pupae and adults, by 65.3, 43.2 and 54.0%, respectively. For the first time, this study showed that bio-priming French bean seeds with bio-inoculants can boost P. vulgaris growth and nodulation, consequently altering its interaction and response to leaf miner infestation, feeding and damage to treated seedlings. These bioinoculants, thus, hold great potential as crop protection agents and could be safely used for priming seeds prior to planting, if leaf mining damages and associated yield losses in French beans are to be minimised in an environmentally sound manner. Further studies should be undertaken to elucidate the mechanisms involved in plant growth promotion, nodulation and insect feeding deterrence.